2018
DOI: 10.1088/1361-648x/aac186
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Li-intercalated bilayer arsenene and hole-doped monolayer arsenene: a first-principles prediction

Abstract: Using first-principles calculations, we find Li-intercalated bilayer arsenene with AB stacking is dynamically stable, which is different from pristine bilayer with AA stacking. Electron-phonon coupling of the stable Li-intercalated bilayer arsenene are dominated by the low frequency vibrational modes (E″(1), [Formula: see text](1), E'(1) and acoustic modes) and lead to an superconductivity with T =  8.68 K with isotropical Eliashberg function. Small biaxial tensile strain (2%) can improve T to 11.22 K due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Since the enhancement of the EPC λ is related to the electron states generated by doping metal atoms near the Fermi level, it had been anticipated that metal atoms (Li, Ca) intercalated in these bilayer systems would give rise to phonon-mediated superconductivity. 11–17 Experiments and theoretical calculations have confirmed the T c at 2 K in Ca-intercalated bilayer graphene (C 6 CaC 6 ). 11 Recent studies examined how the presence of hydrogen adatoms affects the superconducting properties of monolayer MgB 2 , and they found that the electronic density of states at the Fermi level and the electron–phonon coupling, both increase dramatically which in turn enhanced the T c up to 67 K. 18,19…”
Section: Introductionmentioning
confidence: 84%
“…Since the enhancement of the EPC λ is related to the electron states generated by doping metal atoms near the Fermi level, it had been anticipated that metal atoms (Li, Ca) intercalated in these bilayer systems would give rise to phonon-mediated superconductivity. 11–17 Experiments and theoretical calculations have confirmed the T c at 2 K in Ca-intercalated bilayer graphene (C 6 CaC 6 ). 11 Recent studies examined how the presence of hydrogen adatoms affects the superconducting properties of monolayer MgB 2 , and they found that the electronic density of states at the Fermi level and the electron–phonon coupling, both increase dramatically which in turn enhanced the T c up to 67 K. 18,19…”
Section: Introductionmentioning
confidence: 84%
“…The intercalated Li atoms change the interlayer interaction in arsenene from the weak vdW type to the Coulomb type. [86] Zhao et al have studied monolayer As x Sb y alloys, where x and y denote the atomic ratio of As and Sb elements and x + y = 16. The results show that the AsAs and AsSb bonds stabilize the alloy structure while the SbSb bond deteriorates the stability.…”
Section: Band Structure and Optical Propertiesmentioning
confidence: 99%
“…The intercalated Li atoms change the interlayer interaction in arsenene from the weak vdW type to the Coulomb type. [ 86 ] Zhao et al. have studied monolayer As x Sb y alloys, where x and y denote the atomic ratio of As and Sb elements and x + y = 16.…”
Section: Band Structure and Optical Propertiesmentioning
confidence: 99%
“…Another effective way to tune the electronic properties of van der Waals DL is via metal atom intercalation. This has been comprehensively investigated in bilayer graphene [74] and bilayer arsenene [75], and tunable electronic properties and novel superconducting properties are demonstrated in these bilayer systems. Here Na, Mg, and K are acted as the interca lation atoms.…”
Section: Electronic Properties Tuned By Metal Atom Intercalationmentioning
confidence: 99%